Research And Development (R&D) In The Automotive Industry In Malaysia : A Case Of R&D Activities And Issues At The Proton Company - Daulat, Halikhan (2010)
In a dynamic market, firms need to evolve from traditional methods of doing business to contemporary methods that aims at improving the quality of the output. This effort will usually include research and development programmes to introduce new technologies for the new output model. From an automotive industry's perspective, research and development programme is one of the key critical activities that consist of many levels of processes, beginning with brainstorming until vehicle testing.